METHODOLOGICAL BASIS OF PROFESSIONAL PREPARATION OF TEACHING STAFF OF HIGHER EDUCATION INSTITUTIONS - Cherusheva, Galyna; Barvinok, Iryna (Sworld-Us Conference proceedings, 2023)
The work examines the essence of the concept of "professional readiness", its role for the successful professional activity of future teaching staff, substantiated meaningful components of professional readiness, defined individual-personal qualities and